Measuring and Implementing Internet Backbone Security: Current Challenges, Upcoming Deployment, and Future Trends - Matthias Wählisch (2016)
In this thesis, we start from the observation that the Internet is a critical infrastructure, which needs severe protection. We take a practical view on Internet security, considering the whole ecosystem including the network, end devices, and services, protected and threatened by current and future Internet protocols. We contribute tools, methodologies, and measurement results to improve the current state of art as well as operational practice.